2021
DOI: 10.3758/s13423-020-01864-y
|View full text |Cite
|
Sign up to set email alerts
|

Are emojis processed like words?: Eye movements reveal the time course of semantic processing for emojified text

Abstract: Emojis have many functions that support reading. Most obviously, they convey semantic information and support reading comprehension (Lo, CyberPsychology & Behavior, 11[5], 595-597, 2008; Riordan, Computers in Human Behavior, 76, 75-86, 2017b). However, it is undetermined whether emojis recruit the same perceptual and cognitive processes for identification and integration during reading as do words. To investigate whether emojis are processed like words, we used eye tracking to examine the time course of semant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
19
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 44 publications
5
19
0
1
Order By: Relevance
“…With respect to recognition accuracy, results show that, consistent with the levels of processing framework, readers had more accurate recognition memory for emojis that were semantically relevant to the paired text compared to emojis that were not related to the text, suggesting that readers encoded the semantic content of the emojis and integrated it with the surrounding text. The present study extends previous findings suggesting that readers show semantic congruency effects in online processing measures (Barach et al, 2021;Beyersmann et al, 2022) by providing insight about what is retained in memory shortly after reading passages with emojis. Specifically, our findings suggest that readers encode the semantic properties of emojis in memory and show better recognition of semantically congruent emojis compared to semanticallyincongruent emojis after a short delay.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…With respect to recognition accuracy, results show that, consistent with the levels of processing framework, readers had more accurate recognition memory for emojis that were semantically relevant to the paired text compared to emojis that were not related to the text, suggesting that readers encoded the semantic content of the emojis and integrated it with the surrounding text. The present study extends previous findings suggesting that readers show semantic congruency effects in online processing measures (Barach et al, 2021;Beyersmann et al, 2022) by providing insight about what is retained in memory shortly after reading passages with emojis. Specifically, our findings suggest that readers encode the semantic properties of emojis in memory and show better recognition of semantically congruent emojis compared to semanticallyincongruent emojis after a short delay.…”
Section: Discussionsupporting
confidence: 90%
“…Based on the levels of processing framework and prior work showing that readers show semantic congruency effects for emojis during reading (Barach et al, 2021;Beyersmann et al, 2022), we predicted that readers would show higher recognition accuracy for emojis that are congruent with the surrounding passage content (synonym and inference emojis) than incongruent emojis. Extrapolating from the levels of processing framework (Craik and Lockhart, 1972), we also hypothesized a memory advantage for emojis consistent with passage inferences, such that readers would show higher recognition accuracy for inference emojis than for synonym emojis.…”
Section: Present Studymentioning
confidence: 99%
See 1 more Smart Citation
“…However, the direct relationship between emoji congruency and reading remains less understood. To the best of our knowledge, only two prior eye-tracking studies have examined the role of emojis in sentence processing using eye-tracking (Barach et al, 2021; Robus et al, 2020). Robus et al (2020) investigated the effect of emoji valence on text valence but found no evidence for a relationship.…”
Section: Word Congruency Effectsmentioning
confidence: 99%
“…Robus et al (2020) investigated the effect of emoji valence on text valence but found no evidence for a relationship. Barach et al (2021) examined adults’ eye movements on sentences including non-face emojis in sentence final position. Each sentence included a target word ( coffee ) that was either congruent/synonymous ( My tall coffee is just the right temperature ☕) or incongruent with the emoji ( My tall coffee is just the right temperature 🍺), relative to a no-emoji control condition ( My tall coffee is just the right temperature ).…”
Section: Word Congruency Effectsmentioning
confidence: 99%